Image‐based background phase error correction in 4D flow MRI revisited - Busch, Julia; Giese, Daniel; Kozerke, Sebastian (Journal of magnetic resonance imaging, 2017)
Purpose To correct background phase errors in phase‐contrast magnetic resonance imaging (MRI), image‐based correction by referencing through stationary tissue is widely used. The aim of the present study was a detailed assessment of background phase errors in 4D Flow MRI and limitations of image‐based correction. Materials and Methods In a phantom study, 4D Flow MRI data were acquired for typical settings on two clinical 3T MR systems. Background errors were analyzed with respect to their spatial order and minimum requirements regarding the signal‐to‐noise ratio (SNR) and the amount of stationary tissue for image‐based correction were assessed. For in vivo evaluation, data of the aorta were acquired on one 3T MR system in five healthy subjects including subsequent scans on the stationary phantom as reference. Results Background errors were found to exhibit spatial variation of first‐ to third‐order. For correction, a minimum SNR of 20 was needed to achieve an error of less than 0.4% of the encoding velocity. The minimum amount of stationary tissue was strongly dependent on the spatial order requiring at least 25%, 60%, and 75% of stationary tissue for first‐, second‐, and third‐order correction. In vivo evaluation showed that with 35–41% of stationary tissue available only first‐order correction yielded a significant reduction (P < 0.01). Conclusion Background phase errors can range from first to third spatial order in 4D Flow MRI requiring correction with appropriate polynomials. At the same time, the limited amount of stationary tissue available in vivo limits image‐based background phase correction to first spatial order. Level of Evidence: 1 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2017;46:1516–1525.